Thermo-Mechanical analysis of fused filament fabrication process. Issue 1 (February 2020) - Manikandan, N; Vignesh, T; Prasath, C; Ismail, Mohamed
Abstract: Manufacturing industry has been revolutionized by 3D printing or Additive Manufacturing (AM) processes introduced in the late 1980s. Subsequent to intensive research, the technology is even accessed by hobbyists. A layer-by-layer deposition of a material produces a prototype in the commercialized 3-dimensional (3D) printing techniques. Among the 3D printing processes, Fused Filament Fabrication (FFF) or Fused Deposition Modelling (FDM) process is the commonly used process for prototyping, manufacturing functional parts, etc. The process involves the extrusion of a molten polymer filament sequentially through a heated nozzle in the required pattern on to a platform. The FDM process primarily depends on the thermal gradient as the deposited molten material cools, solidifies and bonds with the previous layer. This temperature gradient greatly affects the produced parts microstructure and in turn the macrostructure of the final part. Numerous attempts to experimentally characterize the thermal and mechanical properties of structures fabricated with FDM have been reported in the literature. However, few attempts have been made with 2D models to predict the thermal and mechanical behaviour of the FDM printed components. In this study, a 3D thermo-mechanical model has been developed using ANSYS® workbench using the element birth and death effect. The temperature evolution, maximum principal stress and the deformation due to the thermal gradient were calculated using the developed model. The developed Finite Element Analysis (FEA) model was tested with properties of Poly-Lactic Acid (PLA) material. Through the analysis, it was shown that the model can be used as a predictive tool to understand the thermo-mechanical behaviour of FDM printed parts and also the modelling method used has a great influence on the thermal gradient of the printed parts.